2016
DOI: 10.1111/jog.12966
|View full text |Cite
|
Sign up to set email alerts
|

Relation between time interval from antenatal corticosteroids administration to delivery and neonatal outcome in twins

Abstract: There is a relation between neonatal outcomes in twins and time interval between ACS administration and birth. Therefore, a single ACS course should be administered with caution in order to allow for the completion of the treatment without exceeding an interval of 7 days to delivery. © 2016 Japan Society of Obstetrics and Gynecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A retrospective cohort of 106 twin pregnancies with suspected PTB found that newborns born beyond 7 days after the ACS course experienced increased composite respiratory complications in comparison to those born within 7 days after ACS treatment. 52 We still found a reduction of other adverse outcomes even though the studies were thought to include populations with administration-to-delivery intervals of >7 days. A retrospective study by Rottenstreich et al 53 demonstrated that the rate of optimal initial ACS (ACS administration-to-delivery interval ≥24 hour and ≤7 days) was significantly lower in twin pregnancies than in singletons (19.7% vs 33.2%, p=0.001).…”
Section: Open Accessmentioning
confidence: 81%
“…A retrospective cohort of 106 twin pregnancies with suspected PTB found that newborns born beyond 7 days after the ACS course experienced increased composite respiratory complications in comparison to those born within 7 days after ACS treatment. 52 We still found a reduction of other adverse outcomes even though the studies were thought to include populations with administration-to-delivery intervals of >7 days. A retrospective study by Rottenstreich et al 53 demonstrated that the rate of optimal initial ACS (ACS administration-to-delivery interval ≥24 hour and ≤7 days) was significantly lower in twin pregnancies than in singletons (19.7% vs 33.2%, p=0.001).…”
Section: Open Accessmentioning
confidence: 81%
“…noted significantly reduced RDS in 468 twins after ACS therapy only if the administration‐to‐delivery interval was between 2 and 7 days. Similarly, Kosinska‐Kaczynska et al . showed that delivery within 7 days after ACS therapy significantly influenced the incidence of RDS in preterm twins.…”
Section: Discussionmentioning
confidence: 90%
“…The conclusion that ACS is less effective if administered more than 7 days before delivery remains uncertain, however, even in singletons . In twins, the main studies investigated the efficacy for respiratory complications only . A likely reduction of ACS efficacy after a long administration‐to‐delivery interval particularly justifies exploring the risk–benefit ratio of repeated courses in twin pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…In twin pregnancies, ACS treatment was associated with a decreased rate of RDS and in-hospital mortality when the ACS-to-delivery interval was ≤7 days ( Melamed et al, 2016 ; Palas et al, 2018 ; Vaz et al, 2018 ), even only in the interval between 2 and 7 days ( Kuk et al, 2013 ). In another research, infants in the ACS-to-delivery interval ≥7 days group even suffered from respiratory disorders significantly more often and were hospitalized longer ( Kosinska-Kaczynska et al, 2016 ).…”
Section: Acs Administration Patterns In Twin Pregnanciesmentioning
confidence: 97%